Individual anatomical variability of main craniometric indicators in adult humans. - Vovk, O. Y.; Sukhonosov, R. A. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Despite lots of studies dedicated to the investigation of the skull structure this topic is still of current interest among morphologists. Objective. To establish a range of main craniometric indicators in adult humans including their individual anatomical variability. Methods: external and internal craniometry of skull; stereotopometry; geotopometry; measurements on X-ray images and tomograms; variation-statistical analysis. Results. The study had revealed that the length of the skull in adult men is between 17.0-19.5 cm, for women the range is much smaller – from 16.2 to 17.5 cm. The skull width is less variable: in males – from 13.6 to 15.8 cm, in females – from 13.2 to 14.8 cm. The height of the skull is in the range of sex differences, in males from 14.1 to 15.3 cm, in females – from 13.3 to 15.0 cm. Comparing these figures, it can be argued that adult people has some craniological stabilization depending on gender and age. The range of linear skull parameters is more expressed in men, especially length and less expressed width and height. The cranial index in adult men varies from 71.2 to 88.7, in females – from 72.8 to 87.2; the height-longitudinal index does not exceed 71,8-79,2 and 68.5 -76.9. According to the results of the study three types of structure of the skull were revealed. 1. Brachicranial type – has a rounded skull structure with a characteristic of orthocranial shape by the values of height-longitudinal index in conjunction with tapeynocranial form by height-latitude index; 2. Mesocranial type – has a mesocranial structure of the skull with orthocranial form in conjunction with metriocranial skull shape; 3. Dolichocranial type – is characterized by narrow-skulled structure usually of gypsicranial form (towering) in conjunction with macrocranial form on the specified indices.